1978
DOI: 10.1080/00039896.1978.10667357
|View full text |Cite
|
Sign up to set email alerts
|

Health of Workers Exposed to 1,1,1,–Trichloroethane: A Matched-Pair Study

Abstract: An epidemiologic study of 151 matched pairs of employees was conducted in two adjacent textile plants, one of which used inhibited 1,1,1-trichloroethane as a general cleaning solvent. Employees in the study population had exposures to the solvent for 6 yrs or less at varying concentrations which were measured by breathing zone sampling and personal monitoring. While cardiovascular and hepatic observations were of primary interest, other health parameters were also studied. Application of sensitive statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition to the case reports mentioned, five epidemiologic studies have been found (238)(239)(240)(241)(242). They were published during the period 1975-1988, and there is no indication of increasing research activity in this area despite the increased interest in organic solvents.…”
Section: Passive Smokingmentioning
confidence: 99%
“…In addition to the case reports mentioned, five epidemiologic studies have been found (238)(239)(240)(241)(242). They were published during the period 1975-1988, and there is no indication of increasing research activity in this area despite the increased interest in organic solvents.…”
Section: Passive Smokingmentioning
confidence: 99%
“…Although no adverse effects on the central nervous system were observed in man after chronic exposure to I, I, l-trichloroethane (24,35), exposure to other solvents, such as ethanol, toluene and dichlorornethane, are known to cause cortical impairment (17,31,53). Since long-term exposure to ethanol mainly affects the anterior parts of the cerebral cortex in man (37), different cortical regions were examined in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known of the neuroto xicity of the compound. Studies on workers in occupational settings have been made, and no adverse effects on the central nervous system were observed after chronic exposure (24,35). However, the exposure levelsin these studies were relatively low.…”
mentioning
confidence: 99%
“…Textile workers exposed from several months to 6-years to 1,1,1-trichloroethane concentrations sometimes exceeding 200 ppm revealed no evidence of cardiovascular, hepatic, renal, or other effects as a function of exposure. 19,25 The NIOSH REL for 1,1,1-trichloroethane is a 10-minute ceiling concentration of 350 ppm. 2 The OSHA PEL for 1,1,1-trichloroethane is an 8-hour TWA of 350 ppm.…”
Section: 11-trichloroethanementioning
confidence: 99%